CLASS MANAGEMENT EVALUATION IN IMPROVING EDUCATOR PROFESSIONALISM - Semin, Semin; Patimah, Siti (FKDP (Forum Komunikasi Dosen Peneliti), 2023)
Effective classroom management plays an important role in enhancing the interactions and relationships between teachers and students. An effective classroom management process involves establishing clear rules and procedures, using a variety of learning strategies, and effective communication between teachers and students. In the context of SD IT Cendikia Banjar Agung Tulang Bawang, this study aims to analyze the impact of effective classroom management on improving interaction and relationships between teachers and students. The results of the study show that an effective classroom management process at SD IT Cendikia Banjar Agung Tulang Bawang involves the establishment of clear rules and consistent application. Teachers use a variety of learning strategies to facilitate student involvement in the learning process. In addition, communication between teachers and students is also considered important in creating good relationships. Teachers demonstrated good communication skills in presenting subject matter, listening actively, and providing constructive feedback to students. In the context of increasing interactions and relationships between teachers and students, indicators of effective classroom management include mutual understanding, mutual trust, and active involvement in the learning process. Teachers who are able to listen empathetically, provide individual attention to students, and create an inclusive classroom atmosphere, are able to strengthen the bond between teacher and student. Thus, effective classroom management at SD IT Cendikia Banjar Agung Tulang Bawang has a positive impact on increasing interaction and harmonious relationships between teachers and students.